Niemiecka chadecja wobec konfliktu rosyjsko-ukraińskiego - Bielawska, Agnieszka (Rocznik Integracji Europejskiej, 2015)
This paper presents the positions of German Christian Democrat politicians towards the Russian-Ukrainian conflict and the impact they exert on the activities of the European Union and the Russian Federation. It presents a wide range of opinions and comments of Christian Democrat politicians regarding the political and economic rapprochement of Ukraine with the EU and the crisis in Ukraine between November 2014 and June 2015.